Development and Validation of the Portuguese Transcultural Nursing Leadership Questionnaire (QLTE-PT) - Teixeira, Gisela (2024)
Introduction. This study introduces the Portuguese Transcultural Nursing Leadership Questionnaire (QLTE-PT), a pioneering instrument designed to assess leadership behaviours in multicultural nursing work environments, addressing gaps in current leadership assessment tools. Aim. This study aimed to develop and validate the Portuguese Transcultural Nursing Leadership Questionnaire (QLTE-PT). Methods. It was conducted as a sequential exploratory mixed-method study, integrating DeVellis’s steps for instrument development. Items were formulated based on a literature review and a focus group study, and the content validity was evaluated by a panel of experts. A methodological approach involving nurses registered in the Portuguese Order of Nurses with leadership experience in multicultural nursing work environments was employed to further conduct an exploratory and a confirmatory factor analysis to assess the instrument’s structure and psychometric properties. Results. One hundred forty-five items were initially generated, of which 39 were included in the QLTE-PT following content validity assessment by a panel of experts. EFA revealed a factor structure of 25 items loading on six factors, explaining 64% of the total variance. The overall Cronbach’s α coefficient of the questionnaire was 0.90. This six-factor structure was tested by CFA, revealing a final model of 23 items and six factors, with a good quality of adjustment (CFI = 0.980, TLI = 0.976, SRMR = 0.078, and RMSEA = 0.070). Both convergent and discriminant validity were confirmed. Conclusions. The QLTE-PT demonstrates good psychometric properties and is suitable for assessing transcultural leadership behaviours of nurse managers and leaders in multicultural nursing work environments. Implications for Nursing Management. The QLTE-PT can assist nurse managers to improve their leadership behaviours, promote supportive working environments for their multicultural nursing staff, and improve the quality of care provided to patients from different cultural backgrounds.